1993
DOI: 10.1144/0041395
|View full text |Cite
|
Sign up to set email alerts
|

The link between petroleum emplacement and sandstone cementation

Abstract: When a reservoir fills with petroleum, the process commonly takes about 10 Ma. Cementation of a sandstone reservoir can occur in a similarly short time. There is much direct evidence that these two processes can occur at about the same time. In petroleum-bearing sandstone reservoirs it is common to find inclusions of petroleum trapped in diagenetic minerals. The effect on reservoir porosity and permeability caused by the interaction of these two processes is dramatic. Fields with a relatively early petroleum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
0
22
0
2
Order By: Relevance
“…Some have concluded that petroleum emplacement has no influence on sandstone diagenesis (Taylor et al 2010). Some have concluded that petroleum emplacement stops sandstone diagenesis (Gluyas et al 1993), while others have concluded that sandstone diagenesis can be inhibited (slowed down) by petroleum emplacement (Worden et al 1998;Marchand et al 2001;Worden et al 2018).…”
Section: Open V Closed Systems and Secondary Porositymentioning
confidence: 99%
“…Some have concluded that petroleum emplacement has no influence on sandstone diagenesis (Taylor et al 2010). Some have concluded that petroleum emplacement stops sandstone diagenesis (Gluyas et al 1993), while others have concluded that sandstone diagenesis can be inhibited (slowed down) by petroleum emplacement (Worden et al 1998;Marchand et al 2001;Worden et al 2018).…”
Section: Open V Closed Systems and Secondary Porositymentioning
confidence: 99%
“…The precipitation of quartz overgrowths in many sedimentary basins commonly occurs during deep burial diagenesis (>2.5 km) at elevated temperatures, typically 70 -130 jC (e.g. Giles et al, 1992;Gluyas et al, 1993;Walderhaug, 1994;Bjørkum et al, 1998). Small amounts of quartz cement may, however, develop slowly at lower temperatures ( < 70 jC) given enough time (Bjørkum et al, 1998).…”
Section: Quartz Cementation Conditionsmentioning
confidence: 99%
“…Cementation and oil migration are thought to occur synchronously (Gluyas et al, 1993), but the oil-filling of reservoirs is a gradual process where pores in the crest are filled first (Marchand et al, 2001). Cement growth will therefore cease or slow initially in the crest and continue down the structure until the final oil/water contact is reached.…”
Section: Introductionmentioning
confidence: 99%